Sleep Quality of Elderly with Diabetes Melitus - Citra Windani Mambang Sari; Upi Parida; Dian Adiningsih (Universitas Padjadjaran, 2018)
Diabetes Mellitus (DM) is a chronical community health problem, and mostly suffered by the elderly. The elderly with DM have several symptoms at night that caused a sleep disorder and it may be affected by the poor quality of sleep. The poor quality of sleep has several negative impacts to elderly including sleepy in the daylight, a lack of attention, memory disorders, depression, easy to fall, and reduce of the quality of life. There is a need for a study that assesses the sleep quality of elderly with DM. This study used descriptive quantitative approach. The samples were chosen using total sampling technique. This study involved 47 elderly with DM in the primary health center (PHC) Garuda. The data were collected using Pittsburgh Sleep Quality Index (PSQI) Questionnaire that has been adapted for elders. The data were analyzed using distribution frequency. The results showed that the majority of elderly had a poor sleep quality (51%). All elders in this study had sleep disorders, and some of them had behavior that affected their sleep quality, such as sleeping in a bright room (n=25), sleeping in low temperature room (n=27), and consuming caffeine (n=28). Nurses in the community setting are expected to provide health education to maintenance a good sleep quality, such as the importance of sleeping in the dark and warm temperature room, and avoiding to consume caffeine.